Dentists\' awareness and attitude regarding first dental visit in children - Nasim Seyfi; Milad Nodehghan (Tehran University of Medical Sciences, 2019)
Background and Aims: Tooth decay is still one of the most prevalent pediatric diseases. According to the role of general dentists and importance of first dental visit in prevention, the aim of this study was to evaluate dentist's knowledge and attitude regarding children's first dental visit in Gorgan, Iran. Materials and Methods: In this cross-sectional study, 140 general practitioners participated. In order to assess the level of knowledge, a questionnaire including 2 parts was used as the main tool. Data were analyzed using Mann-Whitney, Kruskal-Wallis and Pearson correlation coefficient. Results: Our findings revealed that the level of knowledge in both sex was equal (P=0.067). There was no significant relationship between the workplace (P=0.68), age (P=0.77), work experience (P=0.84) and the level of knowledge. Interest of practitioners to get the necessary training about examination and treatment of 0-2 year-old children was medium. 51.17% of dentists, admitted the treatment of 8-12 year-old children. 34.5% of dentists revealed that misbehavior of children during treatment was the main reason for unwillingness to accept treating them. 46.9% of dentists, revealed that the most effective result of child's dental visit at an early age is increasing parents' knowledge about prevention of carries in primary dentition. Conclusion: The results showed that general dental practitioners in this study had a good level of knowledge about the first dental visit. Regarding to their little tendency to treat children, it seems necessary to hold workshops and seminars for better desired motivation in this field.